Dynamic NMR microscopy : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Physics at Massey University - Xia, Yang (Massey University, 1992)
The theory and practice of Dynamic NMR Microscopy are described in detail. The description consists of a brief presentation of k-space imaging which includes the 2-D filtered back-projection (PR) reconstruction algorithm as well as the influence of various image contrast factors, a detailed discussion of q-space imaging which employs the Pulsed-Gradient Spin-Echo (PGSE) sequence and a thorough description of Dynamic NMR Microscopy which combines both k-space and q-space mapping. The velocity and self-diffusion image artifacts and errors associated with Dynamic NMR Microscopy have also been investigated extensively. As part of this work, various modifications to and developments of the existing imaging system have been made. These include the probe design for 'non-trivial' flow imaging experiments and software programming using assembly, BASIC, FORTRAN and PASCAL languages. Several instrument-related issues in NMR microscopy have also been investigated. They include the attempt to improve spatial resolution by scaling down the receiver coil, the zero-frequency 'glitch' artifact in images and the effect of induced eddy current in imaging experiments. The results of the comprehensive water capillary flow experiments have shown that simultaneous measurement of velocity and self-diffusion coefficient can be made both accurately and precisely using Dynamic NMR Microscopy. Imaging experiments which investigate molecular motion of relevance to plant physiology, fluid dynamics and polymer physics have been carried out. In the in vivo botanical studies, velocities of approximately 10 µm/s in the castor bean experiment and 45 µm/s in the Stachys experiment have been measured. In the rheological studies, induced secondary flow (eddy) around the abrupt junction in a tube was observed, which has agreed well with numerical simulation of the Navier-Stokes equation. In the studies of unusual rheological properties of high molar mass polymer solutions, velocity profiles for WSR301 polyethylene oxide (PEO)/H2O in capillary flow were measured and fitted using the power law model. The measurement of self-diffusion profiles for monodisperse PEO standards in D2O has shown clear evidence for the breakdown of molecular entanglements in semi-dilute solutions once the shear rate exceeds the equilibrium tube renewal rate, τd-1.
Keywords: Nuclear magnetic resonance; NMR microscopy